Object Scanning of Windows Kernel Driver Based on Pool Tag Quick Scanning (Xibei Gongye Daxue Xuebao, 2019)
In the memory forensics, the Pool Tag Scanning based on the memory pool tag requires a detailed search of the physical memory when scanning the kernel driver object, which is very inefficient. The object scanning of Windows kernel driver by using the pool tag quick scanning is proposed. The method uses the quick pool tag scanning to reduce the memory range of the scan, and then scan the driver object according to the characteristics of the kernel driver object quickly, to help investigator to determine whether the driver is normal. Experimental results shows that the scanning efficiency for object scanning of kernel driver is improved greatly by using the quick pool tag scanning technology and the time spent in the scanning step is reduced while ensuring the false alarm rate is same.